Code mixing among Tunisian university students: types and motivations - Khammari, Hassen (International Journal of Language and Literary Studies, 2023)
The study sheds light on the phenomenon of code mixing among Tunisian university students and the factors motivating it. The study uses a qualitative descriptive approach by describing and analyzing the forms of code mixing used in everyday conversation. Muysken’s (2000) code mixing framework is used to classify and analyze the data. The findings showed that code mixing reflects the Tunisians’ awareness of the bilingual and multicultural nature of society. Code mixing is also a way of gaining social prestige. Mixing codes among friends, in school, in everyday encounters, and even at home is also attributed to the speakers’ innate expectation to use more than one code to communicate and interact.